Exploration of Storytelling Method Implementation to Enhance Language Skills in Lower Grade Elementary School Students - Mawar Febrianti (Riviera Publishing, 2025)
This study aims to explore the implementation of storytelling methods in improving the language skills of low-grade students in elementary schools. The research method used is qualitative descriptive with a case study approach at one of the Hayyan Pengasinan Gunung Sindur Elementary School in Bogor. Data was collected through observation, interviews, and documentation of learning activities. The results of the study show that the application of the storytelling method in a planned and continuous manner can improve students' speaking, listening skills, and expand their vocabulary. Storytelling activities encourage students to be more confident, actively participate, and be able to express ideas in a coherent manner. Teachers also play an important role in creating an interactive learning atmosphere through the use of visual media, intonation, and interesting expressions. In conclusion, storytelling has been proven to be effective in improving the language skills of low-grade students, as well as fostering interest in learning Indonesian from an early age.